Conformable fractional Newton-type inequalities with respect to differentiable convex functions - Cihan Ünal; Fatih Hezenci; Hüseyin Budak (Journal of Inequalities and Applications, 2023)
Abstract The authors propose a new method of investigation of an integral identity according to conformable fractional operators. Moreover, some Newton-type inequalities are considered for differentiable convex functions by taking the modulus of the newly established equality. In addition, we prove several Newton-type inequalities with the aid of Hölder and power-mean inequalities. Furthermore, several new results are given by using special choices of the obtained inequalities. Finally, we give several inequalities of conformable fractional Newton-type for functions of bounded variation.